2020
DOI: 10.3329/bjlr.v0i0.45455
|View full text |Cite
|
Sign up to set email alerts
|

In vitro production of zygote from slaughterhouse driven buffalo oocyte

Abstract: Buffalo is a highly potential animal species in terms of milk and meat production but traditionally they are regarded as poor breeder. In vitro embryos production technology has been introduced in many countries to improve reproductive efficiency of buffalo. Considering the above fact, the present study was undertaken aiming to produce in vitro buffalo embryo in the laboratory. Ovaries of slaughtered buffaloes were collected from abattoir and transported to the laboratory within 4 to 5 hr of slaughter. Cumulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, in buffaloes, the OPU-IVEP efficiency was not affected by the OPU performed on days 1, 3 and 5 of the follicular wave emergences (Gimenes et al 2015). It has also been observed that the number of available follicles was reduced for aspiration during the luteal phase in buffaloes (Deb et al 2020). It may be due to the lutein cells of the corpus luteum (CL) occupying a portion of the ovary that inhibits the follicular development and promotes atresia (Hafez 1993;Deb et al 2020).…”
Section: Hormonal Treatment Aspiration Frequency and Ovarian Status D...mentioning
confidence: 93%
See 3 more Smart Citations
“…However, in buffaloes, the OPU-IVEP efficiency was not affected by the OPU performed on days 1, 3 and 5 of the follicular wave emergences (Gimenes et al 2015). It has also been observed that the number of available follicles was reduced for aspiration during the luteal phase in buffaloes (Deb et al 2020). It may be due to the lutein cells of the corpus luteum (CL) occupying a portion of the ovary that inhibits the follicular development and promotes atresia (Hafez 1993;Deb et al 2020).…”
Section: Hormonal Treatment Aspiration Frequency and Ovarian Status D...mentioning
confidence: 93%
“…It has also been observed that the number of available follicles was reduced for aspiration during the luteal phase in buffaloes (Deb et al 2020). It may be due to the lutein cells of the corpus luteum (CL) occupying a portion of the ovary that inhibits the follicular development and promotes atresia (Hafez 1993;Deb et al 2020). Besides, the progesterone secreted by the lutein cells impedes the follicular development and increases the atresia (Hafez 1993).…”
Section: Hormonal Treatment Aspiration Frequency and Ovarian Status D...mentioning
confidence: 97%
See 2 more Smart Citations
“…In Vitro Produced Calves in and Their Reproductive Fitness had extremely little success with in vitro embryo production in livestock species. Some progress has been made in different aspects, such as buffalo oocyte vitrification [6], in vitro zygote production using slaughterhouse-derived buffalo oocytes [7], in vitro maturation of buffalo oocytes [8], and maturation of goat oocytes [9]. However, none of these endeavors have succeeded in producing in vitrocultured calves.…”
Section: Birth Of Firstmentioning
confidence: 99%